Lesions causing central sleep apnea localize to one common brain network - Yuan, Taoyang; Zuo, Zhentao; Xu, Jianguo (Frontiers in Neuroanatomy, 2022)
Objectives: To characterize the specific brain regions for central sleep apnea (CSA) and identify its functional connectivity network. Methods: We performed a literature search and identified 27 brain injuries causing CSA. We used a recently validated methodology termed “lesion network mapping” to identify the functional brain network subtending the pathophysiology of CSA. Two separate statistical approaches, the two-sample t-test and the Liebermeister test, were used to evaluate the specificity of this network for CSA through a comparison of our results with those of two other neurological syndromes. An additional independent cohort of 6 CSA cases was used to assess reproducibility. Results: Our results showed that, despite lesions causing CSA are heterogeneous for brain localization, they share a common brain network defined by connectivity to the middle cingulate gyrus and bilateral cerebellum posterior lobes. This CSA-associated connectivity pattern was unique compared with lesions causing other two neurological syndromes. The CAS-specific regions were replicated by the additional independent cohort of 6 CSA cases. Finally, we found that all lesions causing CSA aligned well with the network defined by connectivity to the cingulate gyrus and bilateral cerebellum posterior lobes. Conclusions: Our results suggest that brain injuries responsible of CSA are part of a common brain network defined by connectivity to the middle cingulate gyrus and bilateral cerebellum posterior lobes, lending insight into the neuroanatomical substrate of CSA.